Epiphora as first presenting sign of primary extranodal NK/T-cell lymphoma of the lacrimal sac. (2nd January 2017) - Mikhail, Mikel; Michel, René P.; Chankowsky, Jeffrey; Arthurs, Bryan
ABSTRACT: A 28-year-old Caucasian female presented with a six-month history of epiphora of the right eye. Diagnostic lacrimal syringing revealed obstruction of the right nasolacrimal duct. During external dacryocystorhinostomy (DCR), the lacrimal sac had an unusual papillary appearance. Frozen sections suggested malignant lymphoid cells. Pathologic examination revealed extranodal NK/T-cell lymphoma, nasal type. Imaging revealed a mass lesion centered on the lacrimal sac. The authors describe the youngest Caucasian patient with a primary NK/T-cell lymphoma of the lacrimal sac, as well as the first case presenting with epiphora as the sole presenting symptom, reported in the literature. Extranodal NK/T-cell lymphomas rarely occur in the orbit, and are known to be rapidly growing, aggressive lesions. Despite chemotherapy, the patient succumbed to her disease twelve months after diagnosis. Lacrimal surgeons should maintain a high index of suspicion in all cases of primary nasolacrimal duct obstruction. Pre- or intra-operative clinical suspicion of malignancy in the lacrimal sac necessitates biopsy.